The Phenotypic Spectrum of New-onset IBD in Canadian Children of South Asian Ethnicity: A Prospective Multi-Centre Comparative Study. (11th August 2021) - Dhaliwal, J; Carroll, M W; deBruyn, J C; Ricciuto, A; Benchimol, E I; Lawrence, S; Sherlock, M; El-Matary, W; Brill, H; Church, P; Wine, E; Carman, N; et al.
Abstract: Background: Canadian-born children of South Asian [SA] ethnicity develop inflammatory bowel disease [IBD] at similar rates to those among Caucasian children. We evaluated the variation in phenotypic spectrum of IBD in SA and Caucasian children in a national paediatric inception cohort of new-onset IBD. Methods: Patients aged <17 years, enrolled in a Canadian nationwide inception cohort study, were included. Baseline demographic and IBD phenotypic features were compared between SA and Caucasian children. Longitudinal outcomes through 18 months of follow-up were compared matched by propensity scores. Results: Of 1156 children enrolled over 2014 to 2019, 623 were Caucasian [98% and 88% parents Canadian born] and 114 SA [79% Canadian born, 87% parents SA born]. Fewer SAs have a first-degree relative with IBD, 6% vs 19% in Caucasians, p = 0.002. SAs present at a younger age, median age 11.4 years (interquartile range [IQR] 9.2–14.3) vs 13 years [IQR 10.9‐15 years], p = 0.03 and more commonly with a UC/IBD-U [ulcerative colitis/IBD-unclassified] subtype [ratio of UC/IBD-U to CD 1.2:1 vs 1:1.8 for Caucasians, p <0.001]. Additionally, a greater proportion of SA CD patients present with colonic-only disease [colonic-only CD/UC/IBD-U in SAs 67% vs 57% for Caucasians, p = 0.001], and among those with CD, colonic CD in SAs 31% vs 23% in Caucasians, p = 0.20]. Perianal fistulising disease was also numerically more common in SAs (14 [27%] vs 64 [18%], p = 0.06]. Adjusting for differences in phenotypic presentation, anti-tumour necrosis factor [TNF] exposure, and time to initiation was similar, and two-thirds of children, whether anti-TNF exposed or naïve, were in corticosteroid-free clinical remission at 18 months irrespective of ethnicity. Conclusions: The phenotypic spectrum of new-onset IBD in SA children differs from that of Caucasian children, but treatment and clinical course are similar within phenotypic subgroups.